Management of Chronic Infected Intra-Articular Fractures of the Proximal Tibia with Ilizarov Ring Fixation - Bhowmick, Kaushik; Boopalan, P.R.J.V.C.; Gunasekeran, Chandrasekaran; Livingston, Abel; Jepegnanam, Thilak Samuel (The Journal of Knee Surgery, 2020)
Infected nonunion and malunion of tibial plateau are rare injuries with no standardized protocols for treatment. This study assessed the outcome of chronic infected intra-articular proximal tibial fractures with and without metaphyseal bone loss managed with the Ilizarov ring fixator. A series of six patients of intra-articular infected nonunion of the tibial plateau and two patients with malunited plateau with metaphyseal nonunion were treated in a tertiary care hospital. Three of these eight patients had a metaphyseal bone loss or bone gap after debridement and underwent internal transport with distal corticotomy to obtain the bone length. The remaining five patients underwent static ring fixation after correction of the articular deformity. Clinical evaluation was done by Knee Society Score, Rasmussen radiological and Association for the Study and Application of Methods of Ilizarov scores. All patients but one achieved union with the ring fixator. The average follow-up was 33 months (range, 12–120 months). Average time to achieve union was 11.5 months (range, 3–30). The scores were good in four patients and poor in the rest four, out of which three had undergone internal transport. Proximal tibia intra-articular infected nonunion and malunion with or without metaphyseal bone loss can be treated successfully with the Ilizarov fixator. Malunion of the tibial plateau has to be addressed in cases with varus alignment of the limb or articular step-off of ≥ 5mm between the two tibial surfaces. Patients with associated metaphyseal bone loss tend to have complications and take a longer duration to heal. Single-stage treatment avoids intra-articular malunion and loss of limb alignment.
Keywords: nonunion; Ilizarov ring fixation; chronic infected intra-articular fractures of proximal tibia